(untitled) (Revista Argentina de Musicología, 2018)
American origin. The concepts of identity and space are firstly analyzed and deconstructed to define an epistemological basis which allows us to (1) properly embrace the specificity of the study object and (2) solidly explore the connections between sound and society. The common aspects of these identity and space concepts —with roots in musicology and in the cultural sciences—, as well as the possibilities for their application into a spatial-anthropological analysis of a group of electroacoustic pieces, are the key aspects of this discussion. The results are the formulation and development of a typology that contains three original categories: biographical space, porteño space and native space.